2009
DOI: 10.1063/1.3186057
|View full text |Cite
|
Sign up to set email alerts
|

Influence of thermal strains on the electrocaloric and dielectric properties of ferroelectric nanoshells

Abstract: The electrocaloric effect and dielectric tunability of BaTiO 3 ferroelectric nanoshells on Si and MgO cores are investigated using the modified Landau-Ginzburg-Devonshire theory, in which the surface tension and thermal strain are taken into account. The numerical results exhibit a peak of electrocaloric coefficient near the critical nanoshell thickness accompanied with the size-driven phase transition. In addition to the enhanced adiabatic temperature difference, the compressive thermal strain also significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Multi‐physical stimulus can be used to tune/enhance the conventional caloric effect in bulk materials. Researchers have explored the application of both radial and axial compressive stresses to tune the ECE in bulk ferroelectric materials . However, little attention has been paid to the use of hydrostatic pressure to attempt the same.…”
Section: Resultsmentioning
confidence: 99%
“…Multi‐physical stimulus can be used to tune/enhance the conventional caloric effect in bulk materials. Researchers have explored the application of both radial and axial compressive stresses to tune the ECE in bulk ferroelectric materials . However, little attention has been paid to the use of hydrostatic pressure to attempt the same.…”
Section: Resultsmentioning
confidence: 99%
“…displayed that when the grain size of PTO ceramics was reduced to a critical size of 8.8 nm, its spontaneous polarization was suppressed to zero near RT. Dai et al 100 . also found that, at RT, BTO nanoshells with cylindrical cores exhibit an EC coefficient peak with a size‐driven phase transition near the critical nanoshell thickness.…”
Section: Intrinsic Influence Factors Of Materialsmentioning
confidence: 92%
“…Liu et al 94 displayed that when the grain size of PTO ceramics was reduced to a critical size of 8.8 nm, its spontaneous polarization was suppressed to zero near RT. Dai et al 100 also found that, at RT, BTO nanoshells with cylindrical cores exhibit an EC coefficient peak with a size-driven phase transition near the critical nanoshell thickness. The above results indicate that, for optimizing the EC performance of materials with high-phase transition temperatures, such as BTO and PTO, the phase transition temperature can be decreased through the size effect (reduction of grain size), although ΔT will be sacrificed to a certain extent.…”
Section: Grain Sizementioning
confidence: 94%
“…The domain transition temperature is usually close to the ferroelectric transition temperature. Due to the enhancement of depolarization field, the ferroelectric transition temperature decreases when the size of ferroelectrics decreases22. Correspondingly, the domain transition temperature may also decrease with the decrease of size, implying that large ECE is possible to be induced by domain transition near room temperature.…”
mentioning
confidence: 99%